2019
DOI: 10.1089/neu.2018.5956
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assisted Standing Enabled by Non-Invasive Spinal Stimulation after Spinal Cord Injury

Abstract: Neuromodulation of spinal networks can improve motor control after spinal cord injury (SCI). The objectives of this study were to (1) determine whether individuals with chronic paralysis can stand with the aid of non-invasive electrical spinal stimulation with their knees and hips extended without trainer assistance, and (2) investigate whether postural control can be further improved following repeated sessions of stand training. Using a double-blind, balanced, within-subject crossover, and sham-controlled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
212
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 167 publications
(243 citation statements)
references
References 76 publications
(106 reference statements)
9
212
0
4
Order By: Relevance
“…Although recent transcutaneous spinal cord stimulation studies have shown improvement of trunk control during sitting 16 and self‐assisted standing 17 in individuals with SCI, this is the first study to show that tES can facilitate volitional movements in the completely paralyzed leg of a SCI patient after just 16 weeks of stimulation and training. This finding is comparable with previous research using invasive epidural electrical stimulation on a motor complete paraplegic patient regaining volitional movements of lower limbs after stimulation and training 4 .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although recent transcutaneous spinal cord stimulation studies have shown improvement of trunk control during sitting 16 and self‐assisted standing 17 in individuals with SCI, this is the first study to show that tES can facilitate volitional movements in the completely paralyzed leg of a SCI patient after just 16 weeks of stimulation and training. This finding is comparable with previous research using invasive epidural electrical stimulation on a motor complete paraplegic patient regaining volitional movements of lower limbs after stimulation and training 4 .…”
Section: Discussionmentioning
confidence: 70%
“…Transcutaneous electrical stimulation (tES) is a non‐invasive neuromodulation method to activate neural circuits via electric current between a pair of stimulating electrodes placed onto the skin. The tES to SCI patients has recently demonstrated successful activation of motor pools of distal muscles, 7 facilitation for standing, 8 and inducing stepping‐like movements in a gravity‐neutral position 9 . However, tES has not yet exhibited full restoration of voluntary movements of paralyzed limbs, independent full‐weight‐bearing standing, or bipedal stepping without any assistance in paralyzed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the exact mechanism, the ratio between tolerance and spinally evoked motor potentials has to be considered when choosing a stimulation paradigm for studies that require TSS‐induced motor activation for functional outcomes (e.g., for standing such as in Sayenko et al, 2019). On the other hand, previous studies have demonstrated the TSS can be used to facilitate other functions such as rhythmic motions (Gerasimenko et al, 2015), trunk stability (Rath et al, 2018), cardiovascular function (Phillips et al, 2018), and bladder function (Gad et al, 2018) in individuals with spinal cord injury, without directly inducing motor responses.…”
Section: Discussionmentioning
confidence: 99%
“…As such, mechanisms of spinal neuromodulation may also include activation of spinal interneural networks and antidromic activation of ascending fibers in the dorsal columns. TSS has been used to increase excitability at multiple levels of the spinal neuraxis to enable motor and autonomic functions in individuals with chronic spinal cord injury (SCI) (Gad et al, 2018; Hofstoetter et al, 2013, 2015; Minassian et al, 2013, 2016; Phillips et al, 2018; Rath et al, 2018; Sayenko et al, 2019). Although TSS has been examined as a possible clinical intervention for individuals with SCI, the promising findings with regard to motor recovery and the noninvasive nature of the technique could make TSS suitable for use with other neurologically‐impaired populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation